Análisis Del Proceso De Importación De Sustancias Químicas Para Empresas Establecidas En Colombia (2023)
This research aims to inform how to make a proper importation of chemicals taking into account its composition and that meets the requirements of Colombia's regulation. In this sense, to identify the certificates, permits, licenses for its use, and handling or free distribution of this type of products. these requirements determine what is needed for the proper importation of these substances, supply the chemical sector for companies established in Colombia, deal with the precautions and adequate handling that should be given to this type of products.